2023
DOI: 10.3390/medicina59030425
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and the Gluten Free Diet during the COVID-19 Pandemic: Experiences of Children and Parents

Abstract: The COVID-19 pandemic perturbed the everyday life of children and those with chronic illnesses, along with the lives of their families. Patients with celiac disease (CD) follow a strict gluten-free diet (GFD), and gluten ingestion is associated with negative health outcomes. The aim of this study was to investigate the experiences of children with CD and their families concerning their GFD, symptoms and CD management during the first period of the COVID-19 pandemic. A cross-sectional questionnaire-based study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…One possible explanation could be the period of data collection that occurred during the COVID-19 pandemic, but we do not have previous data to compare to the period before the pandemic in Portugal. Theoretically, staying at home favours the time to eat and prepare meals, potentially favouring following a strict gluten-free diet [49,50]. This could potentially reduce the fear of consuming products that contain gluten, but negatively impact the social domain (as occurred in our study) due to the isolation claim during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…One possible explanation could be the period of data collection that occurred during the COVID-19 pandemic, but we do not have previous data to compare to the period before the pandemic in Portugal. Theoretically, staying at home favours the time to eat and prepare meals, potentially favouring following a strict gluten-free diet [49,50]. This could potentially reduce the fear of consuming products that contain gluten, but negatively impact the social domain (as occurred in our study) due to the isolation claim during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 78%
“…This could potentially reduce the fear of consuming products that contain gluten, but negatively impact the social domain (as occurred in our study) due to the isolation claim during the COVID-19 pandemic. A study confirmed that most CD patients felt it was easier to follow the GFD during the pandemic isolation period, consuming meals at home, indicating that eating out is perceived by celiacs as a risk for gluten contamination [50]. However, further study is necessary to verify how the COVID-19 pandemic affected Portuguese celiac patients and compare the periods before, during, and after the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…While the intake of macronutrients and select micronutrients exceeded the RDA in both groups, there remains a need to improve the dietary quality specifically tailored to individuals with CD [ 26 ]. In contrast, a recent report indicates that less than half of CD patients are meeting the recommended daily fruit intake, both before and during the COVID-19 pandemic [ 27 ]. Apparently, the reported controversial results between these studies are likely to be owing to the difference in included population, the method of defining non-adherence, and the method of evaluation of the diet habits and pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the reported controversial results between these studies are likely to be owing to the difference in included population, the method of defining non-adherence, and the method of evaluation of the diet habits and pattern. Nutritious eating hence becomes significantly more critical for patients especially in children and adolescents on highly restrictive diets, such as the GF diet, which typically lacks adequate nutritional quality by nature [ 27 ]. Compliance with a GF diet and the maintenance of a high-quality dietary regimen represent pivotal challenges among children and adolescents diagnosed with CD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kreutz et al haben den klinischen Status bzw. das Beschwerdebild der Kinder nicht erfasst, sodass die klinische Relevanz der von Ihnen erhobenen Nährstoffdefizite offenbleibt [4 .…”
unclassified